Regiospecific analysis by ethanolysis of oil with immobilized Candida antarctica lipase - Shimada, Yuji; Ogawa, Jun; Watanabe, Yomi; Nagao, Toshihiro; Kawashima, Akiko; Kobayashi, Takashi; Shimizu, Sakayu (Lipids, 2003)
Abstract A mixture of oil/ethanol (1∶3, w/w) was shaken at 30°C with 4% immobilized Candida antarctica lipase by weight of the reaction mixture. The reaction regiospecifically converted FA at the 1‐ and 3‐positions to FA ethyl esters, and the lipase acted on C 14 −C 24 FA to a similar degree. The content of 2‐MAG reached a maximum after 4 h; the content was 28–29 mol% based on the total amount of FA in the reaction mixture at 59–69% ethanolysis. Only 2‐MAG were present in the reaction mixture during the first 4 h, and 1(3)‐MAG were detected after 7 h. After removal of ethanol from the 4‐h reaction mixture by evaporation, 2‐MAG were fractionated by silica gel column chromatography. The contents of FA in the 2‐MAG obtained by ethanolysis of several oils coincided well with FA compositions at the 2‐position, which was analyzed by Grignard degradation. It was shown that ethanolysis of oil with C. antarctica lipase can be applied to analysis of FA composition at the 2‐position in TAG.